Quadriplex model enhances urine-based detection of prostate cancer - Jamaspishvili, T; Král, Milan; Khomeriki, Irakli; Vyhnánková, Vlasta; Mgebrishvili, Giorgi; Študent, Vladimír; Kolář, Zdeněk; Bouchal, Jan (Prostate cancer and prostatic diseases, 2011)
BACKGROUND: The major advantages of urine-based assays are their non-invasive character and ability to monitor prostate cancer (CaP) with heterogeneous foci. While the test for the prostate cancer antigen 3 (PCA3) is commercially available, the aim of our research was to test other putative urine markers in multiplex settings (AMACR (α-methylacyl-CoA racemase), EZH2 (enhancer of zeste homolog 2), GOLM1 (golgi membrane protein 1), MSMB (microseminoprotein, β), SPINK1 (serine peptidase inhibitor) and TRPM8 (transient receptor potential cation channel, subfamily M, member 8)). METHODS: Expression of the candidate biomarkers was studied in sedimented urine using quantitative reverse transcriptase polymerase chain reaction in two sets of patients with and without restriction on serum PSA levels. RESULTS: We confirmed that PCA3 is an independent predictor of cancer in the patients without restriction of serum PSA values (set 1, n=176, PSA=0.1-587 ng ml(-1)). However, AMACR was the only parameter that differentiated CaP from non-CaP patients with serum PSA between 3 and 15 ng ml(-1) (set 2, n=104). The area under curve (AUC) for this gene was 0.645 with both sensitivity and specificity at 65%. Further improvement was achieved by multivariate logistic regression analysis, which identified novel duplex (TRPM8 and MSMB), triplex (plus AMACR) and quadriplex (plus PCA3) models for the detection of early CaPs (AUC=0.665, 0.726 and 0.741, respectively). CONCLUSIONS: Novel quadriplex test could be implemented as an adjunct to serum PSA or urine PCA3 and this could improve decision making for diagnostics in the case of 'PSA dilemma' patients.
Keywords: lidé středního věku; Antigens, Neoplasm; Prostate-Specific Antigen; reprodukovatelnost výsledků; mužské pohlaví; Sensitivity and Specificity; Biomarkers, Tumor; časná detekce nádoru; nádory prostaty; Humans; dospělí; senzitivita a specificita; antigeny nádorové; prostatický specifický antigen; Models, Statistical; nádorové biomarkery; statistické modely; lidé; Prostatic Neoplasms; Middle Aged; senioři; Early Detection of Cancer; Reproducibility of Results; Aged; Adult; Male